Animals of the high mountains - Rinard, Judith E. (Washington, D.C. : National Geographic Society, 1989)
Depicts mountain animals from all over the world, including the mountain lion, llama, rock hyrax, and ibex.
Bibliography: p. [34].
Keywords: Mountain animals -- Juvenile literature; Mountain animals